2013
DOI: 10.1371/journal.pone.0084316
|View full text |Cite
|
Sign up to set email alerts
|

First Record of Culicoides oxystoma Kieffer and Diversity of Species within the Schultzei Group of Culicoides Latreille (Diptera: Ceratopogonidae) Biting Midges in Senegal

Abstract: The Schultzei group of Culicoides Latreille (Diptera: Ceratopogonidae) is distributed throughout Africa to northern Asia and Australasia and includes several potential vector species of livestock pathogens. The taxonomy of the species belonging to this species group is confounded by the wide geographical distribution and morphological variation exhibited by many species. In this work, morphological and molecular approaches were combined to assess the taxonomic validity of the species and morphological variants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
46
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 30 publications
(30 reference statements)
5
46
0
Order By: Relevance
“…enderleini (Schultzei group) is also reported in the Afrotropical region and largely dominant in West Africa (Cornet and Brunhes, 1994). This species was recently presented associated with horses in Senegal (Bakhoum et al, 2013;Diarra et al, 2014), has also been recorded in Gambia (Rawlings et al, 1998), in Sudan (Mellor et al, 1984), and is commonly reported in South Africa (Labuschagne et al, 2007;Venter et al, 1996Venter et al, , 2009, Madagascar (Augot et al, 2013), and Zimbabwe (Musuka et al, 2001).…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…enderleini (Schultzei group) is also reported in the Afrotropical region and largely dominant in West Africa (Cornet and Brunhes, 1994). This species was recently presented associated with horses in Senegal (Bakhoum et al, 2013;Diarra et al, 2014), has also been recorded in Gambia (Rawlings et al, 1998), in Sudan (Mellor et al, 1984), and is commonly reported in South Africa (Labuschagne et al, 2007;Venter et al, 1996Venter et al, , 2009, Madagascar (Augot et al, 2013), and Zimbabwe (Musuka et al, 2001).…”
Section: Discussionmentioning
confidence: 76%
“…bolitinos is present in Senegal (Bakhoum et al, 2013;Diarra et al, 2014), Zimbabwe (Musuka et al, 2001), and Madagascar (Augot et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One difficulty as presented by some studies where CO1 sequencing and, perhaps, that of another gene or two is used as a phylogenetic tool is that they often concern relatively small groups of morphologically similar species such as species groups of Culicoides (Ander et al, 2013;Bakhoum et al, 2013;Bellis et al, 2014;Harrup et al, 2016;Muñoz-Muñoz et al, 2014;Pagès et al, 2009;Sarvašová, et al, 2017;Talavera et al, 2017;Tay et al, 2016). Morphologically-based synapomorphies are less likely to be evident (or present) in such similar species groups.…”
Section: Genomes Vs Phenotypementioning
confidence: 99%
“…The scarcity of data on Culicoides taxonomy in Western Africa also complicates identification. Several PCR-based tests were developed for the identification of Culicoides spp., and these tests target the mitochondrial cytochrome oxidase I gene (COI) or the rRNA genes, internal transcribed spacer 1 (ITS-1) or 2 (20)(21)(22)(23)(24)(25)(26).…”
mentioning
confidence: 99%